Analysis of Character Education in the Storybook of The Champion Who Has a Soft Heart by Yusman Nasution (International Journal of Theory and Application in Elementary and Secondary School Education, 2023)
The current era can be witnessed by phenomena shows the decharacterization of the nation. The formation of character of learning is the full responsibility of the teacher then can insert character education through learning that will be delivered to students. The aims of this research are (1) to describe the structure (2) To describe the values of character education in the books (3) Explaining the relevance of learning literature in elementary school. This research uses a qualitative descriptive. Techniques using interviews and document analysis. Data sources include a children's fiction book entitled "The Champion Who Has a Soft Heart" by Yusman Nasution. The results can be concluded (1) 3 children's fiction books has complete of structures (2) There are 9 educational values story entitled "The Champion Who Has a Soft Heart" by Yusman Nasution has religious values, honestly, discipline, hard work, curiosity, repect for achievement, friendly, like to read, and social care. (3) The children's stories from the three books are suitable to be used as literature learning materials in elementary school. This is evidenced by the existence of KD 3.9 Observing the characters 4.9 Delivering the results of identifying characters, especially in IV grade of elementary school.